Changes in Women’s Menstruation Patterns Following COVID-19 Infection - Nisman, Wenny Artanty; Imam Rahmawati, Natasya Putri; Ramadhani, Hanin; Mardliyah, Ainun Saidatul; Kusumawati, Happy Indah; Wibawa, Shinta Restu; Hapsari, Elsi Dwi; Retno, Hersinta (Fakultas Ilmu-ilmu Kesehatan, 2024)
The Coronavirus Disease 2019 (COVID-19) has been demonstrated to disrupt the body's immune response, adversely affecting the reproductive system. Consequently, this study has focused on the changes in the menstruation patterns of survivors of the disease in women of reproductive age with asymptomatic, mild, and severe cases. This study employed an observational cross-sectional approach. The sample comprised 207 women who had recovered from COVID-19 within the past six months and met the inclusion and exclusion criteria. The sampling technique utilized consecutive sampling, and menstrual characteristics were assessed using a questionnaire. Several respondents in the severe group experienced changes in their menstrual patterns. Their duration of menstruation was shortened by 11.11%, and 13.58% had a more extended menstrual period. Some respondents’ cycles were elongated by 20.98%, some decreased their initial menstrual volume by 32.09%, and some increased by 27.16%. Meanwhile, their menstrual volume decreased by 17.28% at the end of menstruation, and their duration lengthened by 24.69%. 12.1% of respondents also reported changes in menstrual regularity. Additionally, 19.75% of respondents stated that their menstrual pain decreased, and 13.58% had increased menstrual pain. The multivariate analysis revealed that the severity of the COVID-19 infection was the primary factor influencing menstrual patterns.